High temperature thermal management with boron nitride nanosheets. Issue 1 (4th December 2017) - Wang, Yilin; Xu, Lisha; Yang, Zhi; Xie, Hua; Jiang, Puqing; Dai, Jiaqi; Luo, Wei; Yao, Yonggang; Hitz, Emily; Yang, Ronggui; Yang, Bao; Hu, Liangbing
Abstract : The rapid development of high power density devices requires more efficient heat dissipation. Abstract : The rapid development of high power density devices requires more efficient heat dissipation. Recently, two-dimensional layered materials have attracted significant interest due to their superior thermal conductivity, ease of production and chemical stability. Among them, hexagonal boron nitride (h-BN) is electrically insulating, making it a promising thermal management material for next-generation electronics. In this work, we demonstrated that an h-BN thin film composed of layer-by-layer laminated h-BN nanosheets can effectively enhance the lateral heat dissipation on the substrate. We found that by using the BN-coated glass instead of bare glass as the substrate, the highest operating temperature of a reduced graphene oxide (RGO) based device could increase from 700 °C to 1000 °C, and at the same input power, the operating temperature of the RGO device is effectively decreased. The remarkable performance improvement using the BN coating originates from its anisotropic thermal conductivity: a high in-plane thermal conductivity of 14 W m −1 K −1 for spreading and a low cross-plane thermal conductivity of 0.4 W m −1 K −1 to avoid a hot spot right underneath the device. Our results provide an effective approach to improve the heat dissipation in integrated circuits and high power devices.